The Attitudes of Teacher Trainees Towards Life Knowledge and Social Studies Teaching Course - S. Gulec; S. Alkis (University of Sofia, 2009)
In Turkey, Social Studies programme basically aims to raise active and productive citizens. This means that teachers are going to inject philosophy of life to the students by means of social studies course. In order to carry out this responsibility, teachers and teachers-to-be should be accustomed to comprehension and learning processes of children and adolescents. By continuous self-improvement, the teachers should try to get more information on methods, materials and tools that can be used in the classroom. A course "Social Studies" gives importance to social behaviour in primary and high schools. This course is given to 1st, 2nd, 3rd grades as "General Life Knowledge" and 4th to 8th grades as "Social Studies". This study aims to investigate the expectations and attitudes of social studies teachers-to-be towards General Life Knowledge and Social Studies Courses in Primary School Teaching Department. 185 students who had taken General Life Knowledge and Social Studies I and II are included in the study. A questionnaire consisting of 40 questions was used as an instrument. In order for this instrument to reflect the real thoughts and feelings of the students, the students are told not to indicate their names in the questionnaire. The students who had taken the questionnaire do not have any anxiety over failing or passing this course because they had already taken and done with these courses for two semesters. The gathered data were analysed in three dimensions: (i) the content and method of General Life Knowledge and Social Studies Course; (ii) the contribution of this course to individuals' being good citizens and socialisation; (iii) Social Studies perception level of Teachers-to-be. It is concluded that teachers-to-be think that the present course is necessary and important, the methods used in teaching social studies are sufficient, materials are not of sufficient amount; it is also indicated they are able to relate their social studies perception levels to their daily lives and, most important of all, they are make deductions about being a good citizen. The other results are presented in detail in the study.